Film Reject Analysis For Conventional Radiography In Khartoum Hospitals - Yousef, Mohamed; Edward, Carolin; Ahmed, Hussin; Bushara, Lubna; Hamdan, Abdullah; Elnaiem, Nasreldin (Asian Journal of Medical Radiological Research, 2013)
It is not uncommon to encounter patients undergo repeat x-ray examinations after their initial x-rays are rejected for poor image quality thereby subjecting them to excess radiation exposure and avoidable extra cost. This creates a situation which necessitates the need to explore causes of reject and repeat of xray examinations. The employment of reject analysis as part of overall Quality Assurance (QA) programmes in clinical radiography and radiology services in the evaluation of image quality is a well-established practice. The role of reject analysis in providing relevant information that would help achieve sound reduction in radiation exposure and cost as well as develop acceptable image quality was explored in this study. To assess the reasons of x-ray films rejection,and to obtain information for further recommendation on qualityin Khartoum state hospitals. Prospective and cross-sectional study approaches were employed. Reject rate was measured for seven x-ray departments across all plain x-ray films examinations using a structured format on which relevant data for reject were recorded by investigators (radiologists and a medical technologists). Results were then collected and entered into a database for analysis.Reject rate along with exposure rate was measured across all plain film exams for the hospitals. Analysis hasshown that the overall reject rate causes: under exposure (26.8 %), over exposure(19.2%), Artifacts (18.7%),patient motion(5.7%), position(23.8%), processing (3.4%) and duplication (2.4%). The major reasons for rejection of ? lms were over- or under-exposure and patient position problems. The study showed the importance of a QA programme in order to deliver high-quality health service to patients.